Memorandum of understanding between Universiti Teknologi MARA and Royal Melbourne Institute of technology (RMIT) / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2018)
UiTM and RMIT will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.